2012
DOI: 10.1002/pmic.201200132
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of interactors for yeast protein arginine methyltransferase Hmt1 reveals novel substrate and insights into additional biological roles

Abstract: Protein arginine methylation is a PTM catalyzed by an evolutionarily conserved family of enzymes called protein arginine methyltransferases (PRMTs), with PRMT1 being the most conserved member of this enzyme family. This modification has emerged to be an important regulator of protein functions. To better understand the role of PRMTs in cellular pathways and functions, we have carried out a proteomic profiling experiment to comprehensively identify the physical interactors of Hmt1, the budding yeast homolog for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Hmt1 was previously shown to catalyze arginine methylation of mRNP components with RGG motifs such as Npl3, Sbp1, and Ded1, which are reportedly localized in RNA granules [ 21 ]. In addition, the P-body component Ebs1 [ 35 ] was recovered in our experiments, confirming the specificity of our screening methods, and Ebs1 was also recovered in proteomic analysis of Hmt1-TAP associating proteins [ 36 ]. These observations suggest the presence of a functional link between Hmt1 and components of P-bodies [ 37 ].…”
Section: Discussionsupporting
confidence: 75%
“…Hmt1 was previously shown to catalyze arginine methylation of mRNP components with RGG motifs such as Npl3, Sbp1, and Ded1, which are reportedly localized in RNA granules [ 21 ]. In addition, the P-body component Ebs1 [ 35 ] was recovered in our experiments, confirming the specificity of our screening methods, and Ebs1 was also recovered in proteomic analysis of Hmt1-TAP associating proteins [ 36 ]. These observations suggest the presence of a functional link between Hmt1 and components of P-bodies [ 37 ].…”
Section: Discussionsupporting
confidence: 75%
“…The ribosomal protein Rps2 is arginine methylated in yeast and humans, albeit by different PRMTs and possibly with different impacts in the two systems [5052]. The Mtr4 RNA helicase was recently shown to interact with the major yeast type I PRMT in vivo , suggesting it might be methylated like its T. brucei homologue [53]. These findings suggest that some functions of arginine methylation exhibit extraordinary evolutionary conservation.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding DNA repair, we identified the DNA excision repair protein, TbSnf2, as an arginine methylated protein. In yeast, Snf2 is associated in vivo with and methylated in vitro by the major type I PRMT, suggesting that modulation of Snf2 function by arginine methylation may be evolutionarily conserved [53]. We detected methylarginine residues in the T. brucei homologues of the PI3K-like kinases, ATM and ATR, which are master regulators of the DNA damage response and repair pathways in other eukaryotes [65].…”
Section: Resultsmentioning
confidence: 99%
“…Ras2p regulates the nitrogen starvation response (Broek et al 1985;Parrini et al 1996) and has been shown to associate with Rmt1p (Jackson et al 2012). The recycling of amino acids is also a component of stationary growth (Herman 2002), and some proteins involved in this process are arginine methylated.…”
Section: Discussionmentioning
confidence: 99%